2017
DOI: 10.1177/0269881117743483
|View full text |Cite
|
Sign up to set email alerts
|

Examining the potential preventative effects of minocycline prescribed for acne on the incidence of severe mental illnesses: A historical cohort study

Abstract: Exposure to minocycline for acne treatment during adolescence appears to have no effect on the incidence of SMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…For instance, two studies concluded that taking minocycline for acne has no protective effect for any mental health conditions including psychosis, while raising the possibility that the observed increase in overall psychiatric morbidity could be due to the “experience of severe acne” itself. [ 23,28 ] Thus, Sellgren et al. wisely cautioned that their study did not provide direct evidence supporting that the observed in vitro effects of minocycline caused the decreased incidence of SZ in their EHR‐based analyses, and that “it is fully possible that minocycline modestly reduces the risk of transition to psychosis… through another as‐yet‐unidentified mechanism”; we concur with this assessment.…”
Section: Is Minocycline's Positive Effect Really Direct or Is It Medmentioning
confidence: 53%
See 1 more Smart Citation
“…For instance, two studies concluded that taking minocycline for acne has no protective effect for any mental health conditions including psychosis, while raising the possibility that the observed increase in overall psychiatric morbidity could be due to the “experience of severe acne” itself. [ 23,28 ] Thus, Sellgren et al. wisely cautioned that their study did not provide direct evidence supporting that the observed in vitro effects of minocycline caused the decreased incidence of SZ in their EHR‐based analyses, and that “it is fully possible that minocycline modestly reduces the risk of transition to psychosis… through another as‐yet‐unidentified mechanism”; we concur with this assessment.…”
Section: Is Minocycline's Positive Effect Really Direct or Is It Medmentioning
confidence: 53%
“…Trials of minocycline and other anti‐inflammatory agents as add‐ons for treating SZ have at‐best produced ambiguous results. [ 22–24 ] Minocycline exerts anti‐inflammatory effects on microglia, but because it also affects other cells of the innate and adaptive immune systems through multiple mechanisms, the experimental use of minocycline to examine a causal role for microglia is problematic. [ 25 ] It remains unknown whether microglia changes observed in individuals with SZ are part of its etiology and pathophysiology or instead a downstream response to some other causal process (see refs.…”
Section: Is Minocycline's Positive Effect Really Direct or Is It Medmentioning
confidence: 99%
“…Moreover, Sellgren et al added analyses of 22,027 electronic health records from two large US medical centers and found an inverse association (HR 0.58, 95% confidence interval (CI) 0.39-0.88) between minocycline and/or doxycycline exposure during adolescence for a minimum of 90 days (3811 individuals) and risk of later diagnosis of nonaffective psychosis, including schizophrenia (F20-F29) [24]. This contrasts an earlier electronic healthcare register study from UK by Herrero-Zazo et al who compared 13,248 minocycline exposed for a minimum of 42 days with 14,393 matched controls and found no preventive effect on SMI from early minocycline prescription [25]. Comparing exposure between these two studies is not entirely trivial.…”
Section: Introductionmentioning
confidence: 71%
“…Although case reports and case series (Kelly et al, 2011; Qurashi et al, 2014; Sura and Bobrin, 2012) and open-label studies (Miyaoka et al, 2008; Miyaoka et al, 2012; Murrough et al, 2018; Soczynska et al, 2014; Soczynska et al, 2017; Vyas et al, 2013) have found adjunctive minocycline to be efficacious and safe for major mental disorders, results of randomized controlled trials (RCTs) have been mixed (Chaudhry et al, 2012; Deakin et al, 2018; Dean et al, 2017; Ghanizadeh et al, 2014; Hu et al, 2017; Husain et al, 2017; Kelly et al, 2015; Khodaie-Ardakani et al, 2014; Levkovitz et al, 2010; Liu et al, 2014; Savitz et al, 2018; Song and Li, 2017; Weiser et al, 2018; Zeng, 2015; Zhang, 2015; Zhang et al, 2018). Furthermore, a study found that minocycline prescribed for acne did not reduce the risk of major mental disorders (Herrero-Zazo et al, 2018). Another study found minocycline had no protective effect on severe psychiatric symptoms in adolescence (Brauer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%